2014
DOI: 10.18632/oncotarget.2013
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic RAS-induced senescence in human primary thyrocytes: molecular effectors and inflammatory secretome involved

Abstract: Oncogene-induced senescence (OIS) is a robust and sustained antiproliferative response to oncogenic stress and constitutes an efficient barrier to tumour progression. We have recently proposed that OIS may be involved in the pathogenesis of thyroid carcinoma by restraining tumour progression as well as the transition of well differentiated to more aggressive variants. Here, an OIS inducible model was established and used for dissecting the molecular mechanisms and players regulating senescence in human primary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 38 publications
2
27
0
Order By: Relevance
“…p16 positive cells were confirmed to be thyroid We then performed p16 immunostaining on tissue serial sections adjacent to those assessed for α-SMA immunostaining ( Figure 4C). We found p16 positive cells in tumor tissues, in agreement with our previous published results [14,15] and localized preferentially at the tumor invasive front (Figure 4C and Figure S4), in agreement with Kim et al [12]. p16 positive cells were confirmed to be thyroid tumor cells through a morphological assessment and the expression of BRAFV600E (assessed by the BRAFV600E-specific monoclonal antibody) and TTF-1 (the thyroid specific transcription factor-1) ( Figure 4C and Figure S4).…”
Section: Senescent Thyrocytes Are Present At the Invasive Front Of Thsupporting
confidence: 93%
See 1 more Smart Citation
“…p16 positive cells were confirmed to be thyroid We then performed p16 immunostaining on tissue serial sections adjacent to those assessed for α-SMA immunostaining ( Figure 4C). We found p16 positive cells in tumor tissues, in agreement with our previous published results [14,15] and localized preferentially at the tumor invasive front (Figure 4C and Figure S4), in agreement with Kim et al [12]. p16 positive cells were confirmed to be thyroid tumor cells through a morphological assessment and the expression of BRAFV600E (assessed by the BRAFV600E-specific monoclonal antibody) and TTF-1 (the thyroid specific transcription factor-1) ( Figure 4C and Figure S4).…”
Section: Senescent Thyrocytes Are Present At the Invasive Front Of Thsupporting
confidence: 93%
“…In this specific case, it is defined as oncogene induced senescence (OIS). The occurrence of OIS in thyroid has been already described in reference [13], as well as by our laboratory [14,15]. Along with cell cycle arrest, confirmed by increased expression of cell cycle inhibitors as p16 INK4a and p21 CIP1 , another feature of senescent cells is to be metabolically active, secreting a myriad of growth factors, cytokines, and chemokines collectively termed SASP (senescence-associated secretory phenotype).…”
Section: Introductionmentioning
confidence: 70%
“…The term "cellular senescence" has been used to describe a state of stable and long-term proliferative arrest, despite maintained viability and metabolic activities [101]. Oncogene-induced senescence (OIS) is a highly stable antiproliferative response to oncogenic stress and acts as an effective barrier to tumor progression [102,103]. In the early stages of tumorigenesis, chemokines such as the CXCL1/CXCR2 axis can mediate OIS through NF-κB signalling to restrict tumor growth.…”
Section: Roles Of Chemokines In Tumor Growth and Proliferationmentioning
confidence: 99%
“…The protective role of IL-6 in OIS, as discussed below, occurs naturally in pituitary adenomas as a dynamic and slow mechanism, which results in a benign tumor with stable growth arrest. Interestingly, in other endocrine tumors like thyroid nodules, IL-6 (and its receptor) expression (Ruggeri et al 2002) and also OIS with an associated inflammatory secretome (Vizioli et al 2014) has been reported, suggesting that a senescence process involving IL-6 might also take place in thyroid tumor progression.…”
Section: Autocrine Il-6 Mediates Pituitary Tumor Senescencementioning
confidence: 99%